Enhancing EFL Students Listening Comprehension Through Cloze Dictation: A Quasi-Experimental Study - Nur Halima Malik; Jamiluddin; Mashuri; Muhammad Arid (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study examines the effectiveness of the cloze dictation technique in improving the listening comprehension of EFL students, focusing on common problems including poor vocabulary identification, trouble capturing crucial information, and lack of focus during listening tasks. Two sets of eleventh-grade students were used in a quasi-experimental design: a control group (n = 35) was taught using traditional listening techniques, while an experimental group (n = 34) received instruction using cloze dictation. Pre-test and post-test listening assessments were used to gather data, and descriptive and inferential statistics were used for analysis. The results showed that whereas the control group made no discernible gain (from 58.86 to 56.71), the experimental group exhibited a significant increase, with the mean score rising from 60.44 to 73.38. The Mann-Whitney U test verified a statistically significant difference between the two groups (p = 0.006 < 0.05) because the data were not normally distributed. The findings show that the cloze dictation method successfully improves students' capacity to recognize spoken words, concentrate on important details, and derive meaning from auditory input. Pedagogically, this study highlights the importance of integrating structured and interactive listening activities to promote active engagement and deeper comprehension in EFL classrooms. Practically, English teachers are encouraged to incorporate cloze dictation regularly using varied and level-appropriate audio materials to support students’ listening development. Future research is recommended to explore the integration of this technique with other language skills or across different educational contexts to further validate its effectiveness.